2021
DOI: 10.1039/d1an00872b
|View full text |Cite
|
Sign up to set email alerts
|

Ambient electric arc ionization for versatile sample analysis using mass spectrometry

Abstract: A novel, convenient ambient electric arc ionization (AEAI) device was developed as mass spectrometry ion source for versatile sample analysis. AEAI could be considered as a soft ionization technique in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…14,17,18,23 In addition, arc discharge can induce the formation of nitrate ions that are MS detectable in negative ion mode. 24 Herein, we describe the development of a highly sensitive and selective atmospheric pressure arc desorption/ionization MS (APADI-MS) approach for the analysis of explosives on various surfaces, using arcinduced nitrate ions as reagents to form detectable adducts with explosives. We found that in APADI arc discharge ion sources, anionic additives actually could not bind with explosives to form characteristic adducts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14,17,18,23 In addition, arc discharge can induce the formation of nitrate ions that are MS detectable in negative ion mode. 24 Herein, we describe the development of a highly sensitive and selective atmospheric pressure arc desorption/ionization MS (APADI-MS) approach for the analysis of explosives on various surfaces, using arcinduced nitrate ions as reagents to form detectable adducts with explosives. We found that in APADI arc discharge ion sources, anionic additives actually could not bind with explosives to form characteristic adducts.…”
mentioning
confidence: 99%
“…For discharge-type ion sources (e.g., corona and glow discharge), nitrogen oxide anion additives are not beneficial to non-nitrate adducts such as [M+Cl] − . ,,, In addition, arc discharge can induce the formation of nitrate ions that are MS detectable in negative ion mode . Herein, we describe the development of a highly sensitive and selective atmospheric pressure arc desorption/ionization MS (APADI-MS) approach for the analysis of explosives on various surfaces, using arc-induced nitrate ions as reagents to form detectable adducts with explosives.…”
mentioning
confidence: 99%
“…Although ESI is considered to be one of the most commonly used commercial ionization source, compounds with low polarity suffer from low ionization efficiency in ESI, leading to low sensitivity and repeatability. , Hence, an improved approach with a high detection sensitivity for such compounds has been highly anticipated. Among numerous plasma-based ion source, the arc-plasma device has been shown to perform well for analysis of low-polarity compounds. The mechanism of the arc-plasma ionization primarily relies on a high voltage applied between the electrodes, which leads to the breakdown of air in the electrode gap. It generates high voltage and high-frequency arcs and a series of reactive species that react with the analyte and produce ions.…”
Section: Resultsmentioning
confidence: 99%
“…Primarily, [H 2 O] n H + interacts with the analyte (M), resulting in the formation of the protonated analyte ([M + H] + ; eq ). Abundant production of radical cations (N 2 + , NH + , O 2 + , NO 2 + , O 2 H 2 O + , and O 4 + ) through arc discharge indicates the occurrence of the APCI mechanism in AESI normalM + false[ H 2 normalO false] n H + false[ normalM + normalH false] + + n H 2 normalO …”
Section: Resultsmentioning
confidence: 99%
“…Plasma discharge techniques, such as corona discharge, dielectric barrier discharge, microwave-induced discharge, glow discharge, and arc discharge, offer direct means of sample ionization. Applying plasma to ESI enhances ionization efficiency, provides instant detection, and heightens sensitivity compared to other ESI techniques .…”
mentioning
confidence: 99%